Ontologies of Drug Discovery and Design for Neurology, Cardiology and Oncology - M. Vazquez-Naya, Jose; Martinez-Romero, Marcos; B. Porto-Pazos, Ana; Novoa, Francisco; Valladares-Ayerbes, Manuel; Pereira, Javier; R. Munteanu, Cristian; Dorado, Julian (Current Pharmaceutical Design, 2010)
The complex diseases in the field of Neurology, Cardiology and Oncology have the most important impact on our society. The theoretical methods are fast and they involve some efficient tools aimed at discovering new active drugs specially designed for these diseases. The ontology of all the items that are linked with the molecule metabolism and the treatment of these diseases gives us the possibility to correlate information from different levels and to discover new relationships between complex diseases such as common drug targets and disease patterns. This review presents the ontologies used to process drug discovery and design in the most common complex diseases.
Keywords: Drug Interaction Ontology (DIO)